Self-Esteem, job motivation, behaviour and performance nexus among electrical installation and maintenance work teachers in technical colleges - Chinyere Theresa Ogbuanya (Konselor, 2022)
The study investigated the moderating roles of self-esteem and gender in the relationship among job motivation, job behaviour and job performance of electrical installation teachers in Technical Colleges, Nigeria. The study adopted correlational design in conducting the research. The study was guided by four hypotheses. The population for the study was all 111 electrical installation teachers across South-West technical colleges. All the 111 electrical installation teachers across South-West technical colleges participated in the study. The instrument used for data collection in the study was a questionnaire and was validated by three experts. An internal consistency test result indicated 0.79 for job motivation, 0.83 for job behaviour, 0.84 for job performance and 0.77 for self-esteem. Data collected from the study was analyzed using Pearson Product Moment Correlation (PPMC) and BC bootstrap from PROCESS macro. The major findings of the study established that self-esteem and gender significantly moderated the relationship between job motivation and behavior, job motivation and performance, as well as between job behavior and job performance. Based on the findings of the study, it was recommended that special attention should be placed on developing electrical installation teachers self-esteem in order to improve their possible job related behaviour and performance. It was also recommended that physiological interference of gender should be carefully studied among electrical installation teachers in order to enhance approximately equal performance from teachers and other employees.